Peran Institusi Internasional Dalam Penanggulangan Ancaman Cyber - Iqbal Ramadhan (Populis : Jurnal Sosial dan Humaniora, 2017)
This article describes about managing cyber threat by using the role of international institution. Cyber threat is borderless and state is hard to maintain its security in digital age. Managing cyber threat is not like arms control. It also cannot rely on realist’s self-help concept because the threat comes from state and non-state actor. In order to anticipate the threat, cooperation through international institution is very important. The state actor can share information and cooperate in managing the threat by using international institution. In South East Asia, ASEAN Economic Community must be supported by stable cyber environment. Indonesia and other members should work together to prevent any cyber threat that can jeopardize ASEAN Economic Community.